2021
DOI: 10.1177/27324745211014154
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning and Students With Extensive Support Needs: (Re)Defining Access to Education From a Distance

Abstract: Students with Extensive Support Needs (ESN) experience multiple barriers in accessing distance learning educational programs during school closures in the context of the COVID-19 pandemic. These barriers include inaccessible formats, a lack of access to adequate support to access instruction, and a lack of available assistive technology. Access issues may result in further isolation of students and reduced access to general education peers and curriculum. Promising practices include close collaboration with fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 40 publications
(47 reference statements)
2
12
0
1
Order By: Relevance
“…Second, participants reported that parents of students with SD were overwhelmed and frustrated and described internalizing this frustration. These findings are consistent with research describing the overwhelming stress parents experienced as they supported their children engaged in online instruction, while maintaining other roles [11,13]. However, this study provides a unique look into the experiences of parents of students with SD as parents and other family members (siblings) assumed a fulltime co-teaching role with participants.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Second, participants reported that parents of students with SD were overwhelmed and frustrated and described internalizing this frustration. These findings are consistent with research describing the overwhelming stress parents experienced as they supported their children engaged in online instruction, while maintaining other roles [11,13]. However, this study provides a unique look into the experiences of parents of students with SD as parents and other family members (siblings) assumed a fulltime co-teaching role with participants.…”
Section: Discussionsupporting
confidence: 88%
“…School closures caused by COVID-19 also took a toll on families. Family caregivers (hereafter referred to as "parents") were immediately forced to prioritize the competing demands associated with caregiving, employment, general household responsibilities, and, as a result of COVID-19, educating their children [10][11][12]. Parents also assumed the role of "student", as they learned how to engage their children in online instruction [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is only verbal modeling that is provided via video conferencing formats; the participants’ children could not observe or interact with their peers as they would in the classroom. The findings highlighted decreased inclusive education and increased social isolation, confirming challenges faced by students with ESN and their families during nontraditional education (Hanreddy, 2022).…”
Section: Discussionmentioning
confidence: 72%
“…Аналогично в уязвимой позиции оказались учителя, особенно старшей возрастной группы с низким уровнем цифровой компетенции. Чрезмерная интенсификация работы учителя инициирует такие негативные последствия, как имитация деятельности, профессиональное выгорание [12].…”
unclassified